Nachhaltigkeit durch kommunale Abgaben: am Beispiel des Kampfes gegen Plastikmüll - Kahl, Wolfgang (EurUP, 2019)
Klaus Lange has made an outstanding contribution to both municipal and environmental law. Within both areas one of his main scientific interests was and still is municipal taxes and duties. The latter not only are an important instrument for the municipalities and especially their finances but also for an effective and efficient environmental policy (sustainable development). This is underlined by recent political developments such as the proposed local exercise duty on certain single-use plastic products in Tübingen. In principle, municipal taxes and duties can play a meaningful role in fighting plastic waste. Nonetheless, there are also constitutional limits to be taken into account. The following contribution looks at both – chances and limits of municipal duties in the field of waste policy.
Gesehen am 03.01.2020